Articulating the unique competencies of admiral nurse practice. Issue 3 (11th September 2018) - Carter, Christine; Bray, Jennifer; Read, Kate; Harrison-Dening, Karen; Thompson, Rachel; Brooker, Dawn
Abstract : Purpose: The purpose of this paper is to describe the process of developing a contemporary competency framework for admiral nurses in dementia care. Design/methodology/approach: Information and evidence was gathered from research and policy literature regarding competencies to deliver advanced practice within dementia care. An online survey completed by 75 admiral nurses with follow-up interviews clarified current practice across the range of service contexts in which they work. A focus group (FG) of people living with dementia and family carers, and a reference group of practitioners helped to develop a competency framework which was refined through FGs with admiral nurses working in different areas. Findings: The literature review, survey and interviews provided a framework grounded in up-to-date evidence and contemporary practice. There was broad agreement in the literature and the practitioners' priorities regarding the core competencies of advanced practice, with constructive suggestions for making the framework useable in practice. This resulted in a robust framework articulating the competencies of admiral nurses which could be used for continuous professional development. Originality/value: Engaging the admiral nurses ensured the competencies were contemporary, succinct and applicable within practice, and also cultivated a sense of ownership. Developing the competency framework with the admiral nurses not for them provides an approach which may have value for professionals undertaking a similar process in their specialist area. It is anticipated the competency framework will provide further evidence of the benefits of specialist nurse support for families affected by dementia.